2020
DOI: 10.1002/art.41293
|View full text |Cite
|
Sign up to set email alerts
|

Biologics May Prevent Cardiovascular Events in Rheumatoid Arthritis by Inhibiting Coronary Plaque Formation and Stabilizing High‐Risk Lesions

Abstract: Objective To evaluate whether biologic disease‐modifying antirheumatic drugs (DMARDs) decrease cardiovascular disease (CVD) risk in rheumatoid arthritis (RA) and whether biologic DMARDs might have a beneficial effect on coronary plaque formation or progression. Methods In this single‐center observational cohort study, 150 patients underwent computed tomographic angiography for evaluation of coronary atherosclerosis (total, noncalcified, mixed/calcified, and low‐attenuation plaque); 101 had repeat assessments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 50 publications
2
32
2
2
Order By: Relevance
“…Collectively, these data speak to several study findings 33 34 indicating benefits of RA therapies not only include effect on systemic inflammation, 35 but cardiometabolic profile 36 and a targeted effect on key immune mediators of CVD. Similarly, a prospective cohort study suggested that after accounting for other risk factors and treatment response, subjects actively receiving bDMARDs experienced lower CV event risk, which was not observed in those who discontinued.…”
Section: Discussionsupporting
confidence: 61%
“…Collectively, these data speak to several study findings 33 34 indicating benefits of RA therapies not only include effect on systemic inflammation, 35 but cardiometabolic profile 36 and a targeted effect on key immune mediators of CVD. Similarly, a prospective cohort study suggested that after accounting for other risk factors and treatment response, subjects actively receiving bDMARDs experienced lower CV event risk, which was not observed in those who discontinued.…”
Section: Discussionsupporting
confidence: 61%
“…Another recent CTA study by Karpouzas et al, in the same population, proposes bDMARD use to slow the coronary atherosclerosis in RA patients. 37 In the present study, we found a tendency of increased odds for CACS ≥ 400 and obstructive CAD in RA patients on csDMARD treatment, which was not seen in patients on bDMARD treatment. However, due to few patients, the estimates for bDMARDs presented with 95% CIs ranging from a small negative to a strong positive association.…”
Section: Discussioncontrasting
confidence: 42%
“…However, the risk score demonstrated good fit in subanalyses of patients who were and were not receiving statins. The MBDA-based CVD risk score accounts for the level of inflammation, the treatment of which has potential to reduce CVD risk in RA patients [21][22][23]. The score may have utility for RA patients who are receiving statins because the statin dose may not yet have been optimized and because the non-statin treatment options for elevated CVD risk in RA patients may include DMARDs.…”
Section: Discussionmentioning
confidence: 99%
“…Synovial and systemic inflammation in RA patients contribute to CVD risk independently of traditional risk factors [4]. In observational studies, the risk for CVD events was greatest in RA patients with high disease activity [16][17][18][19][20] and effective RA treatment appeared to reduce the risk for atherosclerosis [21] and CVD events [22,23]. Traditional CVD risk factors, such as diabetes, may be exacerbated by RA-related mechanisms [24,25].…”
Section: Introductionmentioning
confidence: 99%